2021
DOI: 10.1021/acs.jpcc.1c08736
|View full text |Cite
|
Sign up to set email alerts
|

Room Temperature Migration of Ag Atoms to Cover Pd Islands on Ag(111)

Abstract: The structures of Pd islands at three different Pd coverages (0.028, 0.064, and 0.150 monolayer (ML)) on Ag(111) were studied at room temperature with scanning tunneling microscopy (STM). While previous studies have shown that the structure and composition of Pd islands on Ag(111) change at elevated temperatures, we found that Ag atoms migrate to cover the Pd islands even at room temperature. These Ag atoms occupy sites in the middle of the islands, and second layer growth begins at these sites. The migration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 34 publications
(84 reference statements)
1
15
1
Order By: Relevance
“…These differences in bond distance strongly indicate the presence of heteroatomic bonding in the SD- x : y -Ag:Pd/carbon samples. Notably, lower CN values are seen for Ag–M than Pd–M for samples with low Pd loadings, which suggests that Pd atoms are predominantly in subsurface locations in these clusters (despite being reduced onto the Ag) and Ag atoms dominate the surface in these samples . This is consistent with the observation made recently by Gedara et al that Ag atoms can migrate to cover Pd islands on Ag(111) in minutes at room temperature . However, this trend reverses at higher Pd loadings, and much lower Pd-M CNs are seen for Pd-rich AgPd clusters which suggests most Pd is on the surface of such clusters (Scheme ).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…These differences in bond distance strongly indicate the presence of heteroatomic bonding in the SD- x : y -Ag:Pd/carbon samples. Notably, lower CN values are seen for Ag–M than Pd–M for samples with low Pd loadings, which suggests that Pd atoms are predominantly in subsurface locations in these clusters (despite being reduced onto the Ag) and Ag atoms dominate the surface in these samples . This is consistent with the observation made recently by Gedara et al that Ag atoms can migrate to cover Pd islands on Ag(111) in minutes at room temperature . However, this trend reverses at higher Pd loadings, and much lower Pd-M CNs are seen for Pd-rich AgPd clusters which suggests most Pd is on the surface of such clusters (Scheme ).…”
Section: Resultssupporting
confidence: 86%
“…40 This is consistent with the observation made recently by Gedara et al that Ag atoms can migrate to cover Pd islands on Ag(111) in minutes at room temperature. 47 However, this trend reverses at higher Pd loadings, and much lower Pd-M CNs are seen for Pd-rich AgPd clusters which suggests most Pd is on the surface of such clusters (Scheme 1). We note that while the Ag−M CN increases slightly for the SD-1:6-Ag:Pd/carbon sample, there is still a reasonable amount of Ag on the surface of all particles.…”
Section: Resultsmentioning
confidence: 99%
“…For Ag(111), we reported the height of Ag-encapsulated Pd islands to be 0.420 nm and Patel et al reported 0.459 nm high Ag-capped Pt-rich islands for Pt deposited on Ag(111). 16,47 However, we note that conclusions based on heights alone are not definitive as the Au−Pd interlayer interaction could make the height of a Au-capped Pd island different from what is expected based on assuming that layer heights are simply additive. Because the formation of the Au-capped Pd islands is not accompanied by the formation of vacancy pits, the Au atoms likely detach from step edges and diffuse onto the Pd islands.…”
Section: ■ Experimental Sectionmentioning
confidence: 62%
“…15 Previously, we reported a scanning tunneling microscopy (STM) study of the evolution of the structure of Pd islands on Ag(111) with time and upon annealing to different temperatures. 16 In this study, we compare and contrast the behavior of Pd on the Au(111) and Ag(111) surfaces. The thermodynamics of Pd on Ag(111) and Au(111) favors diffusion of Pd into the bulk of the substrate because of the higher surface free energy of Pd (2.0 J m −2 ) than that of Ag (1.3 J m −2 ) and Au (1.6 J m −2 ).…”
Section: ■ Introductionmentioning
confidence: 99%
“…CO causes Pd segregation into the topmost surface layer [ 32 ]. The strong effects of reactive gases such as CO or O 2 on the alloy structure and composition were investigated by scanning tunneling microscope (STM) and Fourier transform infrared spectroscopy (FTIR) to illustrate the correlation of chemical properties with structural aspects of bimetallic surfaces of a given composition at ambient pressure [ 33 , 34 , 35 ]. Theoretical calculations show that the driving force for the structural reconstruction is the strong interaction of the surface Pd sites with the adsorbed CO molecules, which changes the surface energy and leads to surface segregation of Pd [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%